Förster resonant energy transfer in quantum dot layers - Bradley, Louise (My University, 2010)
Förster resonant energy transfer (FRET) in quantum dot (QD) layer structures has been analyzed. Small and large colloidal CdTe QDs were used as donors and acceptors, respectively. A FRET theory for random donor/acceptor distributions in two dimensions, taking into account exclusion zones around the donors, was applied to characterize FRET in a mixed monolayer. The exclusion zones provide a possibility to include the QD size in the FRET analysis and to determine its impact on the FRET efficiency. The acceptor concentration dependence of the FRET efficiency can also be described within this theory. In a separate donor/acceptor layer structure the distance dependence of the FRET efficiency as well as the acceptor enhancement was investigated. Both were found to agree well with the model of FRET between donor and acceptor layers.
Keywords: Förster resonant energy transfer; Colloidal nanocrystals; Optical spectroscopy; Time-resolved photoluminescence